Antibacterial and antifungal properties of the methanol extract from the stem of Argyreia argentea - Rahman, Md. Atiar; Ahsan, Taslima; Islam, Saiful (Bangladesh Journal of Pharmacology, 2010)
Antibacterial properties of methanol extract of Argyreia argentea stem was studied on Gram positive and Gram negative bacteria by disc diffusion method. The extract showed zone of inhibition against Gram positive bacteria (Bacillus cereus, B. subtilis, B. megaterium and Staphylococcus aureus) and Gram negative bacteria [E. Coli, Salmonella typhae, S. paratyphae, Pseudomonous sp. (I), Pseudomonous sp. (II) and Shigella sonnei]. In addition, the extract was found effective against some fungi like Aspergillus flavous, Fusarium equiseti, Altenaria alternate, Aspergillus niger, Colletotrichum corphori.